1974
DOI: 10.2135/cropsci1974.0011183x001400020026x
|View full text |Cite
|
Sign up to set email alerts
|

Soil and Symbiotic Nitrogen Requirements for Optimum Soybean Production1

Abstract: Field and outdoor hydroponic studies were conducted to determine the relative potential of soybeans (Glycine max L. Merr.) to utilize nitrate and atmospheric nitrogen as sources of nitrogen. Comparisons of nodulating and nonnodulating isollnes coupled with enzymatic assays of nitrate reductase (in vivo) and nitrogenase (in situ acetylene reduction) were used as indexes. Seasonal profiles indicate maximunmit rate utilization at the full‐bloom growth stage, with symbiotic N2(C2H2) fixation peaking some 3 weeks l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
126
1
16

Year Published

1977
1977
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 207 publications
(153 citation statements)
references
References 0 publications
10
126
1
16
Order By: Relevance
“…As a first approximation, we would expect that the actual magnitude ofnitrate reduction in an organ was proportional to the NRA in that organ. Harper (9) has shown for soybeans that although the in vivo NR assay integrated over time overestimates the actual accumulation of reduced N, it nevertheless is an excellent predictor of reduced N. We expect that in KNO3-treated seedlings, a greater proportion of N03 was reduced in shoots, and in NaNO3-treated seedlings, a greater proportion of N03 was reduced in roots.…”
Section: Resultsmentioning
confidence: 94%
“…As a first approximation, we would expect that the actual magnitude ofnitrate reduction in an organ was proportional to the NRA in that organ. Harper (9) has shown for soybeans that although the in vivo NR assay integrated over time overestimates the actual accumulation of reduced N, it nevertheless is an excellent predictor of reduced N. We expect that in KNO3-treated seedlings, a greater proportion of N03 was reduced in shoots, and in NaNO3-treated seedlings, a greater proportion of N03 was reduced in roots.…”
Section: Resultsmentioning
confidence: 94%
“…Studies including field-measured data of postharvest N 2 O emissions are reviewed in the next section. Harper (1973). We believe that the growth pattern of soybeans in the two studies were similar since Yang and Cai (2005) reported their pod-filling stage occurred at day 82 whereas Harper (1973) stated that N 2 fixation rate peaked at the pod-filling stage (approximately day 85).…”
Section: Nodule Decomposition In Soybeans and N 2 O Emissionsmentioning
confidence: 84%
“…1a; Yang and Cai 2005). According to Harper (1973), soybean N requirements peaked at the full-bloom growth stage and soybean N fixation peaked during the pod-filling stage (Fig. 1b).…”
Section: Nodule Decomposition In Soybeans and N 2 O Emissionsmentioning
confidence: 89%
“…Nitrogen fixation, however, may reach its peak during pod fill for soybean (Harper 1974), cowpea and chickpea (Cicer arietinum L.) (Wery et al 1988). Thus, the crop may fail to respond to additional soil nitrate because of restricted uptake during pod fill (Nelson-Schreiber and Schweizer 1986) but could still benefit from a more efficient or prolonged N2-fixation system.…”
mentioning
confidence: 99%